Upaya Meningkatkan Komunikasi Matematika Siswa SMP Dengan Menerapkan Model Pembelajaran Kooperatif Tipe Think-Pair-Share - 'Afifah, Nur; Dachi, Surya Wisada; Harahap, Tua Halomoan (Journal Mathematics Education Sigma [JMES], 2024)
The aim of this research is to find out how to improve students' mathematical communication by implementing the think-pair-share cooperative learning model. This research is Classroom Action Research (PTK) carried out in junior high schools. The research subjects were 32 class VIII students consisting of 16 men and 16 women. The object of the research is students' independent mathematics learning in think-pair-share type cooperative learning. This research consists of 2 cycles, namely each cycle consists of 3 meetings. Student learning independence tests are carried out at the beginning and end of each cycle. The student mathematics communication test consists of 6 questions. The results of the research are that there is an increase in junior high school students' mathematical communication. Supported by the results of research on the cognitive aspect, namely the results of students' mathematical communication tests at the end of cycle I, with an average of 57.09 and classical completeness of 56.25%, and a gain index of 0.47 with moderate improvement criteria. The students' mathematics communication test results at the end of cycle II were an average of 67.81, and classical completeness was 87.50%, and a gain index of 0.57 with moderate improvement criteria. Based on the results of the research, the researchers suggest mathematics learning by implementing the think-pair-share cooperative learning model, as input for schools to improve students' mathematical communication, learning quality and innovation, as input for teachers in an effort to improve teachers' abilities in managing learning So that student activity in learning also increases, mathematics learning by implementing the think-pair-share type cooperative learning model prioritizes students being able to communicate and learn independently, and it is hoped that future researchers will be able to adapt the steps in this research and correct deficiencies. in this research.